FAST-NEPAL: Regionally Calibrated Spectral Method for Reinforced Concrete With Masonry Infills - Cross, Theodore; De Luca, Flavia; Woods, Gregory E. D.; Giordano, Nicola; Pokhrel, Rama Mohan; De Risi, Raffaele (Frontiers in Built Environment, 2022)
Reinforced concrete (RC) with masonry infill is one of Nepal's most common structural typologies, especially in the Kathmandu Valley. Masonry infills are typically made of solid clay bricks produced locally in Nepal. This study aims to calibrate the spectral-based analytical method FAST for Nepalese RC infilled buildings. FAST method has been initially conceived for Southern European RC buildings with hollow clay brick infills. This is achieved by reviewing code prescriptions and construction practices for RC masonry infills in Nepal and updating the FAST method. The FAST method variables are calibrated using different information sources and employing a Bayesian updating procedure to consider global and local material properties. The FAST-NEPAL method obtained is then verified considering a single school design, for which a detailed state-of-the-art vulnerability assessment is available. Being particularly suitable for large-scale assessment, the method is further validated using data of Ward-35 of Kathmandu Metropolitan City (in the vicinity of Tribhuvan international airport) obtained from photographic documentation included in a geo-referenced database of buildings collected after the Nepal 2015 earthquake and prepared for census purposes. The comparisons showed that the FAST-NEPAL method can be conservative relative to the other data sources for vulnerability but is more accurate at capturing low-level damage. This makes the approach suitable for large-scale preliminary assessment of vulnerability for prioritization purposes.